1998
DOI: 10.1002/(sici)1096-9861(19980202)391:1<42::aid-cne4>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Localization of glial cell line-derived neurotrophic factor receptor alpha and c-ret mRNA in rat central nervous system

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is a neurotrophic factor that influences the survival and function of several neuronal populations in the central (CNS) and peripheral nervous systems. The actions of GDNF are mediated by a multicomponent receptor complex composed of the tyrosine kinase product of c-ret and the ligand-binding protein GDNF receptor alpha (GDNFR-alpha). In the present study, we used in situ hybridization to localize cells expressing the mRNA for these GDNF receptor subunits in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 35 publications
10
79
0
Order By: Relevance
“…The diverse biological actions of GDNF are mediated through its RET receptor tyrosine kinase (Trupp et al, 1996;Yu et al, 1998;Paratcha et al, 2001) and RET protein has been found expressed in the mesencephalic dopaminergic neurons and their striatal terminals, but not in the intrastriatal neurons (Trupp et al, 1997;Golden et al, 1998;Tsuzuki et al, 1995;Glazner et al, 1998;Walker et al, 1998;Honda et al, 1999;He et al, 2008). However, in our hand, it was possible to detect RET protein in the striatum but not in the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse biological actions of GDNF are mediated through its RET receptor tyrosine kinase (Trupp et al, 1996;Yu et al, 1998;Paratcha et al, 2001) and RET protein has been found expressed in the mesencephalic dopaminergic neurons and their striatal terminals, but not in the intrastriatal neurons (Trupp et al, 1997;Golden et al, 1998;Tsuzuki et al, 1995;Glazner et al, 1998;Walker et al, 1998;Honda et al, 1999;He et al, 2008). However, in our hand, it was possible to detect RET protein in the striatum but not in the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
“…Here we examined the effects of LY379268 treatment on activation levels of RET Tyr1062 in both substantia nigra and striatum, since RET protein has been found in the mesencephalic dopaminergic neurons and their striatal terminals (Tsuzuki et al, 1995;Glazner et al, 1998;Walker et al, 1998;Honda et al, 1999).…”
Section: Ret Receptor Activation By Ly379268 Was Time-related To Gdnfmentioning
confidence: 99%
“…The GDNF receptor complex consists of two components, GFR␣-1 and the Ret receptor, both of which are expressed by nigral DA neurons. [62][63][64] While the expression of GFR␣-1 and Ret have not been examined in the aged rat brain, age-related alterations in the distribution or expression of the GDNF receptor complex may reduce the protective effects of GDNF in the lesioned SN.…”
Section: Discussionmentioning
confidence: 99%
“…Ret (Fig. 2 E) and GFR␣1 (Glazner et al, 1998;Mikaels et al, 2000) are abundantly expressed in most neurons of both these nuclei, and Ret-deficient mice no longer express any active Ret receptors, so the differences in dependency does not reflect distinct expression and/or localization of the receptor as a consequence of the lesion. GDNF expressed in Schwann cells is rapidly upregulated after sciatic nerve lesion with peak levels at 7 d and soluble GFR␣1 released from these cells may act on regenerating motor axons (Naveilhan et al, 1997;Fundin et al, 1999;Paratcha et al, 2001).…”
Section: Motor Neuron Survival By Gdnf Family Ligand Signaling Via Retmentioning
confidence: 99%